Predictors of Attempted Suicide Among Youth Living With Perinatal HIV Infection and Perinatal HIV-Exposed Uninfected Counterparts. (1st December 2021) - Kreniske, Philip; Mellins, Claude Ann; Dolezal, Curtis; Morrison, Corey; Shea, Eileen; Fisher, Prudence W.; Kluisza, Luke; Robbins, Reuben N.; Nguyen, Nadia; Leu, Cheng-Shiun; Wiznia, Andrew; Abrams, Elaine J.
Abstract : Background: Suicide is a leading cause of death among adolescents and young adults (AYA). AYA living with perinatally acquired HIV infection (AYALPHIV) are at higher risk of attempted suicide when compared with AYA who were perinatally HIV-exposed but uninfected (AYAPHEU). To inform interventions, we identified risk and protective factors of attempted suicide among AYALPHIV and AYAPHEU. Setting: Data were obtained from a longitudinal New York City–based study of AYALPHIV and AYAPHEU (n = 339; enrollment age 9–16 years) interviewed approximately every 12–18 months. Method: Our main outcome was suicide attempt at any follow-up. The DISC was used to assess psychiatric disorder diagnoses and attempted suicide and the Child Depression Inventory to assess depressive symptoms. Psychosocial and sociodemographic risk factors were also measured. Analyses used backward stepwise logistic regression modeling. Results: At enrollment, 51% was female individuals, 49% Black, 40% Latinx, and 11% both Black and Latinx. Attempted suicide prevalence was significantly higher among AYALPHIV compared with AYAPHEU (27% vs 16%, P = 0.019), with AYALPHIV having 2.21 times the odds of making an attempt [95% confidence interval: (1.18 to 4.12), P = 0.013]. Higher Child Depression Inventory scores were associated with an increased risk of attempted suicide in both groups and the total sample. The presence of DISC-defined behavior disorder increased the risk of attempted suicide in the total sample and the AYALPHIV subgroup. Religiosity was protective of attempted suicide in AYALPHIV. Conclusions: AYALPHIV had increased suicide attempts compared with AYAPHEU. Religiosity was protective in AYALPHIV. Highlighting a need for prevention of early mental health challenges was associated with risk.